Techno feudalism what killed capitalism - Varoufakis, Yanis (Brooklyn Melville House, 2024)
In a revelatory and pathbreaking work, the #1 international bestselling economist opens our eyes to the new power that is reshaping our lives and the world. No one noticed when capitalism was ... replaced. Perhaps we were too distracted by the pandemic, or the endless financial crises, or the rise of TikTok. But under cover of them all, a new and more exploitative system has been taking hold. Insane sums of money that were supposed to re-float our economies went to big tech instead. Having privatised the internet, big tech has been able to replace capitalism's twin pillars - markets and profit - with its platforms and rents. With every click and scroll, we labour like serfs to increase its power. Welcome to technofeudalism: the new power that is reshaping our lives and the world, and the greatest current threat to social democracy. Drawing on stories from Greek Myth and pop culture, from Homer to Mad Men, world-famous economist Yanis Varoufakis explains this revolutionary transformation: how it enslaves our minds, how it rewrites the rules of global power and ultimately what it will take overthrow it"
Includes index
Keywords: Capitalism